2011
DOI: 10.1159/000323264
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence on Mitochondrial Targeting of β-Amyloid and Specificity of β-Amyloid-Induced Mitotoxicity in Neurons

Abstract: Background/Aims: Impaired mitochondrial function has been described in Alzheimer’s disease. We previously reported that, in neuronal cells, β-amyloid 1–42 (Aβ1–42) is targeted to mitochondria. We have also reported that, when incubated with isolated rat brain mitochondria, Aβ1–42 inhibits complex IV, uncouples the mitochondrial respiratory chain, and promotes opening of the membrane permeability transition pore. Here, we further analyzed the targeting and mitotoxicity of Aβ1–42 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Release of MDH was measured upon interaction of mitochondrial suspensions (1 mg/ml) with 10 lM of Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) fibrillation products corresponding to 0 h (monomer), 24 h, 1 week, 2 weeks, 3 weeks, and 1 month of incubation. [72][73][74] Meanwhile, Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) has shown to significantly decrease the activity of CS and all respiratory chain complexes and cause a generalized loss of mitochondria in neurons. Data are expressed as mean 6 STD with n 5 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Release of MDH was measured upon interaction of mitochondrial suspensions (1 mg/ml) with 10 lM of Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) fibrillation products corresponding to 0 h (monomer), 24 h, 1 week, 2 weeks, 3 weeks, and 1 month of incubation. [72][73][74] Meanwhile, Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) has shown to significantly decrease the activity of CS and all respiratory chain complexes and cause a generalized loss of mitochondria in neurons. Data are expressed as mean 6 STD with n 5 6.…”
Section: Discussionmentioning
confidence: 99%
“…2,71 Accordingly, it has been suggested that Ab toxicity is mediated via effects on mitochondria. [72][73][74] Meanwhile, Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) has shown to significantly decrease the activity of CS and all respiratory chain complexes and cause a generalized loss of mitochondria in neurons. 75 We assumed that the increased surface hydrophobicity of Ab(25-35) peptide upon amyloid formation enhanced capability of the peptide to interact with the lipid bilayers, resulting in mitochondrial membrane disruption.…”
mentioning
confidence: 99%
“…Tillement et al. reported that Aβ(1–42) accumulated in mitochondria and did not induce apoptosis even at 10 μ m , although Meng et al. observed Aβ‐induced apoptosis .…”
Section: Figurementioning
confidence: 99%
“…Aβ 1–42 peptides are imported into the mitochondria via the translocase of the outer membrane import machinery and localizes to mitochondrial cristae [107]. The translocation of Aβ 1–42 peptides into mitochondria has been linked to mitotoxic effects by in vitro and in vivo evidence, such as increased release of adenylate kinase and ROS, and this mitotoxicity is promoted by aging [108,109,110]. Calcium influx is one of the mitotoxic effects induced by Aβ 1–42 , and evidence suggests that oxidative stress and the subsequent neurodegeneration induced by accumulation of Aβ 1–42 peptides are calcium influx-dependent (Figure 2) [111,112,113].…”
Section: The Potential Of the Mcu As A Target For Neurodegenerativmentioning
confidence: 99%